A Systemic Review on Comparative Study of Traditional And Modern Methods of Preparation of Ayurvedic Medicines - Parul Rani; Mandeep Jaiswal; Dinesh Kumar Maurya; Anil Kumar Varshney; Nitin Sharma; Ashish Kumar Tripathi (AYUSHDHARA, 2023)
Affordable, high-quality Ayurvedic remedies may be the answer to today's healthcare demands of the Indian and worldwide communities. In order to scale up manufacturing of the medications, which is required to satisfy the rising demand, it is vital to relate Ayurvedic preparations with modern processing principles. For bettering the dosage forms, it's also crucial to comprehend the basic Ayurvedic concepts behind formulation and processing. There has been no systematic research to compare ancient and contemporary processing methods, despite the fact that the Ayurvedic sector has included technology from the food, chemical, and pharmaceutical industries. This study makes an effort to show a potential relationship between modern processing principles and Ayurvedic processing techniques. By gathering data from English translations of old Ayurvedic writings on medication preparation techniques, a thorough literature analysis was carried out to determine the Ayurvedic processing procedures. Based on the methods employed in Ayurvedic medication processing, a correlation between traditional and modern processing principles was conducted. Extraction and separation were found to be the two main types of procedures used in the manufacture of Ayurvedic medicines. Separation employs volatility, adsorption, and size-exclusion principles whereas extraction relies on membrane rupturing and solute diffusion principles. The study offers systematic recording of the Ayurvedic processes for making Ayurvedic medicines, coupled with an explanation of those processes in terms of modern processing principles. This is the initial stage that can lead to the advancement or replacement of conventional methods.